Scientific background of precision animal nutrition - Babinszky, László (Acta Agraria Debreceniensis, 2012)
Precision animal nutrition consists of meeting the nutrient requirements of animals as accurately as possible in the interest of a safe, high-quality and efficient production, besides ensuring the lowest possible load on the environment. This is facilitated by electronic feeding based on IT technology, an important but by far not the only tool of precision nutrition. In the present paper the following most important elements of precision nutrition are discussed: diet formulation, quality control of ingredients and compound feeds, reduction of the harmful effects of heat stress in pigs with different nutritional tools, application of the recent findings of the molecular genetics in animal nutrition, the relationship between genetics and animal nutrition and reduction of the N and P excretion by nutritional tools.